Molecular insight into the viral biology and clinical features of trichodysplasia spinulosa. (1st March 2016) - Wu, J.H.; Nguyen, H.P.; Rady, P.L.; Tyring, S.K.
Summary: Trichodysplasia spinulosa (TS) is a disfiguring skin disease that occurs most frequently in patients receiving immunosuppressive therapies, and is thus frequently associated with organ transplantation. TS is characterized clinically by folliculocentric papular eruption, keratin spine formation and development of leonine face; and histologically by expansion of the inner root sheath epithelium and high expression of the proliferative marker Ki‐67. Recent discovery of the TS‐associated polyomavirus (TSPyV) and emerging studies demonstrating the role of TSPyV tumour antigens in cell proliferation pathways have opened a new corridor for research on TS. In this brief review, we summarize the clinical and histological features of TS and evaluate the current options for therapy. Furthermore, we address the viral aetiology of the disease and explore the mechanisms by which TSPyV may influence TS development and progression. As reports of TS continue to rise, clinician recognition of TS, as well as accompanying research on its underlying pathogenesis and therapeutic options, is becoming increasingly important. It is our hope that heightened clinical suspicion for TS will increase rates of diagnosis and will galvanize both molecular and clinical interest in this disease.